Tailoring biochar for persulfate-based environmental catalysis: Impact of biomass feedstocks - Song, Ge; Qin, Fanzhi; Yu, Jiangfang; Tang, Lin; Pang, Ya; Zhang, Chen; Wang, Jiajia; Deng, Lifei (Journal of hazardous materials, 2022)
Biochar, a carbonaceous material with engineering potential, has gained attention as an efficient catalyst in persulfate-based advanced oxidation processes (PS-AOPs). Although biomass feedstocks are known as a critical factor for the performance of biochar, the relationship between the catalytic efficiency/mechanism and the types of biomass feedstocks is still unclear. Thus, according to recent advances in experimental and theoretical researches, this paper provides a systematic review of the properties of biochar, and the relationship between catalytic performance in PS-AOPs and biomass feedstocks, where the differences in physicochemical properties (surface properties, pore structure, etc.) and activation path of different sourced biochars, are introduced. In addition, how the tailoring of biochar (such as heteroatomic doping and co-pyrolysis of biomass) affects its activation efficiency and mechanism in PS-AOPs is summarized. Finally, the suitable application scenarios or systems of different sourced biochars, appropriate methods to improve the catalytic performance of different types of biochar and the prospects and challenges for the development of biochar in PS-AOPs are proposed. [Display omitted] •The similarities and differences of various sourced biochar are discussed detailly.•Feedstocks have crucial impacts on catalytic performance of biochar based PS-AOPs.•The effect of activation efficiency by biochar tailoring has been fully clarified.•Biochar from various sources is suitable for different occasions or systems.•Insights for oriented tailoring of different sourced biochars are provided.